Ball Milling Synthesis of Silica Nanoparticle from Rice Husk Ash for Drug Delivery Application - Salavati-Niasari, Masoud; Javidi, Jaber; Dadkhah, Mahnaz (Combinatorial Chemistry & High Throughput Screening, 2013)
Silica nanoparticles were synthesized from rice husk ash at room temperature by using high energy planetary ball mill. The milling time and mill rotational speed were varied in four levels. The morphology of the synthesized powders was investigated by the FE-SEM and TEM image as well as XRD patterns. The results have revealed that the nano-sized amorphous silica particles are formed after about 6 h ball milling and they are spherical in shape. The average particle size of the silica powders is found to be around 70 nm which decreases with increasing ball milling time or mill rotational speed. The as-synthesized silica nanoparticles were subsequently employed as drug carrier to investigate in vitro release behavior of Penicillin-G in simulated body fluid. UV-Vis spectroscopy was used to determine the amount of Penicillin-G released from the carrier. Penicillin-G release profile from silica nanoparticles exhibited a delayed release effect.
Keywords: rice husk ash